2017
DOI: 10.1021/acssuschemeng.7b01378
|View full text |Cite
|
Sign up to set email alerts
|

Ecofriendly Mechanochemical Extraction of Bioactive Compounds from Plants with Deep Eutectic Solvents

Abstract: A fast, highly efficient, and ecofriendly extraction method using deep eutectic solvents (DESs) for mechanochemical extraction (MCE) was developed to extract bioactive compounds from plants. Tea leaves containing bioactive compounds such as alkaloids, flavonoids, and catechins were used to evaluate this method. Dozens of DESs and DESs/water mixtures were systematically studied and optimized to select optimized extraction conditions. The results showed that the extractions can be completed within 20 s. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(37 citation statements)
references
References 21 publications
0
35
0
Order By: Relevance
“…DESs are generally produced by mixing two or more components that are capable of self-association to form a eutectic mixture with a melting point that is below that of the individual compounds [33]. Hydrogen-bonding interactions are the main diving force of this phenomenon [34].…”
Section: Supermolecular Structure Of La-buta Desmentioning
confidence: 99%
“…DESs are generally produced by mixing two or more components that are capable of self-association to form a eutectic mixture with a melting point that is below that of the individual compounds [33]. Hydrogen-bonding interactions are the main diving force of this phenomenon [34].…”
Section: Supermolecular Structure Of La-buta Desmentioning
confidence: 99%
“…Previous studies reported the application of DES-MW/US for the extraction of polyphenols, flavonoids and alkaloids from various vegetable or waste biomasses, confirming the positive role of a combined chemical and thermal approach. 40,41,42,43 In fact, similarly to conventional ILs, DES can be efficiently coupled with MW irradiation due to their polar nature. Especially organic acid-based DES, which show the highest polarity.…”
Section: Lipid Extraction By Dmcmentioning
confidence: 99%
“…However, when the water content exceeded 70%, the extraction efficiencies decreased rapidly. This result may be caused by the destruction of the DES structure and resulted in the solubility reduction in DES of hyperoside and isoquercitrin . Therefore, DES‐5 (with 70% water) can be used to extract hyperoside and isoquercitrin.…”
Section: Resultsmentioning
confidence: 99%
“…Chen and his partners have used DESs‐mechanochemical extraction method to extract bioactive compounds such as flavonoids from plants. The extraction can be completed within 20 s with high efficiency . In comparison with the conventional solvents such as methanol, DESs had advantages of fast extraction speed, high efficiency for target ingredients, and low toxicity for environment and humans.…”
Section: Introductionmentioning
confidence: 99%